Mendobrak Hambatan Membangun Jembatan: Pendekatan Sosial Kognitif untuk Kesiapan Kerja bagi Penyandang Disabilitas Fisik Melalui Pelatihan Digital - Hanifah Herawati; Muhammad Sidiq; Seyska Islamida Rahma (Jurnal Bengawan Solo Pusat Kajian Penelitian dan Pengembangan Daerah Kota Surakarta, 2025)
People with physical disabilities in Indonesia continue to face structural inequalities in accessing the labor market, which leads to low levels of economic independence. This study aims to analyze the impact of applying social cognitive theory in digital skills training as an empowerment strategy for individuals with physical disabilities, in order to enhance their readiness to meet the demands of the modern workforce. The research employs a descriptive qualitative method, with data collected through in-depth interviews, direct observation, and documentation. The research informants consist of students with physical disabilities, supporting teachers, dormitory supervisors, and the principal of YPAC Special School in Surakarta. Data validity is strengthened through triangulation of techniques and sources. Data analysis follows the interactive model of Miles, Huberman, & Saldaña, which includes four stages: data collection, reduction, presentation, and verification. The results indicate that the application of social cognitive theory through an innovative concept called the motivation layer comprising three layers: internal self-belief reinforcement, social support, and public validation significantly contributes to increased self-confidence, technical skills, and job readiness among participants. The observed psychological transformation and active participation in the digital sphere demonstrate that training based on social cognitive theory not only bridges the skills gap but also breaks down the psychosocial barriers that have long restricted the mobility of individuals with physical disabilities. The findings recommend that similar training models be implemented on a wider scale to foster an inclusive and sustainable employment ecosystem.